Does self-paced learning in mobile flood protection unit construction in virtual reality have advantages over traditional measures? - Querl, Patrick; Chandra, Raymond Leonardo; Berkaoui, Djamel; Castermans, Koen; Nacken, Heribert (Frontiers in Virtual Reality, 2024)
This study examines the use of virtual reality (VR) as an application example in university education using an immersive virtual lab employing self-paced learning in the field of civil engineering. The study focuses on the construction of a Mobile Flood Protection Unit (MFPU), a task that is traditionally taught through written instructions or video tutorials. The authors conducted an experiment in which 48 students were divided into two groups to learn how to build an MFPU using a VR tutorial and a traditional instructional video. The effectiveness of these teaching tools was evaluated in terms of factual and procedural knowledge transfer. In addition, the students' personal perception of the use of the VR software was evaluated. A positive effect on factual knowledge transfer and a positive reception of students towards using VR were observed, while further studies are needed about the knowledge gain on the procedural level.